Experience in the treatment of patients with fusiform aneurysms of cerebral vessels - D.V. Shchehlov; Ya.E. Kudelskyi; O.A. Pastushyn; O.E. Svyrydiuk; O.M. Goncharuk (Ендоваскулярна нейрорентгенохірургія, 2020)
Objective – to analyze there sults of treatment of patients with fusiform aneurysms (FA) depending on localization and type of surgery. Materials and methods. In the period from 2007 to 2019 127 patients with intracranial fusiform cerebral aneurysms underwen treatment in Scientific and Practical Center of Endovascular Neuroradiology of the National Academy of Medical Sciences of Ukraine. 133 fusiform aneurysms were identified. The following neuroimaging methods were used to diagnose FA: magnetic resonance imaging, multispiral computed tomography and cerebral selective angiography according to Seldinger. In this study, patients with fusiform aneurysms are divided according to localization in the FA of the carotid poolsand the FA of the vertebrobasilar basin. Patients with FA of carotid basins were 56 (27 (29 (51.8 %) men and 48.2 %) women). The average age of patients was 45.2 year. 31 (55.3 %) patients were operated. Patients with FA in the vertebrobasilar basin were 71 (43 (60.6 %) men and 28 (39.4 %) women). The average age of patients was 54.5 year. It was operated 48 (67.6 %) patients. Results. It was possible to completely eliminate FA from the bloodstream intraoperative in 16 (51.6 %) patients. In the early postoperative period in this group 5 (16.1 %) patients had a decrease in disease symptoms, in 3 (9.6 %) patients neurological symptoms increased. In other patients the dynamics of neurological manifestations remained unchanged. There were nofatal out comes in either the early or late post operative period. According to the extended Glasgow outcome scale at the time of discharge from the hospital 22 (71 %) patients had > 5 points, 9 (29 %) – 4 points. In the period from 3 to 5 weeks 2 symptomatic thromboses of flow-directingstents were noted, in the form of clinical manifestations of ischemic stroke. In the period from 3 to 6 months 22 (71 %) patients underwent control examination. Angiographically in 19 (86.3 %) revealed a completes hut down of FA from the bloodstream, in 3 (13.7 %) – decrease of volume of FA > 65 %. Clinical symptoms completely regressed in 16 (72.7 %) patients, partially regressed – in 3 (13.7 %), increased – in 2 (13.6 %). In the period from 12 to 18 months 7 (31.8 %) patients underwent control examination. Total FA shut down from the bloodstream was detected in 5 (71.4 %) patients, in 2 (28.6 %) aneurysms decreased by 80 %. Eighteen-month survival was 100 %. It was possible to intraoperatively switch off FA in the vertebrobasilar basin from the bloodstream in 11 (22.9 %) cases. In the early postoperative period a partial regression of neurological symptoms was observed in 7 (14.5 %) patients. In 10 (20.8 %) cases a new or increasing neurological deficit was observed after intracranial stent implantation, which partially regressed against the background of conservative treatment. Four (8.3 %) deaths were recorded in the early postoperative period. The clinical results of 48 patients on the Glasgo woutcome scale at the time of discharge were > 5 points in 27 (56.2 %) patients, 4 points – in 17 (35.4 %) and 1 points – in 4 (8.3 %). In the period from 3 to 6 months 19 (39.5 %) patients underwent control examination. Angiographically in 14 (73.7 %) patients the aneurysm was completely turned off from the blood circulation, in 2 (10.5 %) the decrease in the volume of the aneurysm was > 70 %, in 3 (15.8 %) patients the decrease in the volume of the aneurysm was 47–64 %. Clinical symptoms regressed in 7 (36.8 %) patients, a decrease in neurological deficit was noted in 2 (10.5 %) patients, an increase in neurological deficit in 3 (15.8 %) patients. Three deaths were recorded. In the period from 12 to 18 months, 12 (25 %) patients underwent control examination. Angiographically in 10 (83.3 %) patients FA was excluded totally from the bloodcirculation, in 2 (16.7 %) – the volume of aneurysm was reduced by 80 %. Clinical symptoms regressed in 8 (66.6 %) patients and increased in 1 (8.3 %). During the control period 2 patients died. The 18-month survival rate was 89.5 %, 5 (10.5 %) patients died. Conclusions. Fusiform aneurysms are more common in people of working age, more common in men. A more unfavorable course of the disease occursin patients with symptomatic FA of the vertebrobasilar basin, due to the compression and dysfunction of the brainstem and stem structures. Deconstructive methods for eliminating FA from the bloodstream provide long-termsatis factory treatment results, butrequire careful selection of patients for such in terventions. Endovascular treatment should be considered as the main treatment, asitentails fewer risks for the patient. For aneurysms that cannot be treated with endovascular methods, microsurgical treatments hould be considered. The main forsuccess ful treatment of patients with fusiform aneurysms is th ecareful selection of patients and individual approach to the choice of treatment based on the shape, location and size of the FA.